ESR Investigations of (BaSnO3)x/(Cu, Tl) 1223 composite in the normal and superconducting state. (3rd April 2021) - Srour, A.; Basma, H.; Noureldeen, S.; Malaeb, W.; Awad, R.
ABSTRACT: (BaSnO3 )x /Cu0.5 Tl0.5 Ba2 Ca2 Cu3 O10-δ superconducting composites (0.00 ≤ x ≤ 1.50 wt.%) were prepared by the solid-state reaction technique. The crystalline structure and superconducting transition temperature were investigated by X-ray powder diffraction (XRD) and dc-electrical resistivity measurements, respectively. X-Band electron spin resonance (ESR) measurements were carried out at different temperatures 103 ≤ T ≤ 298 K. ESR spectra are dominated by a single asymmetric line corresponding to Cu 2+ ions at the rhombic site. The temperature dependence of the g factors allowed the determination of the pseudo-gap onset temperature T*. The results of T* are compatible with those obtained from resistivity and thermoelectric power measurements. The contribution of delocalized electrons from Cu 2+ ions in the disordered part of the impurity phases BaCuO2 and Ba2 CuO3 is significant for the high addition of nanoparticles. Moreover, the number of spins N participating in ESR and the activation energy Ea were enhanced with the addition of BaSnO3 .